Nitrous Oxide Emissions from Paddies: Understanding the Role of Rice Plants - Timilsina, Arbindra (Plants (Basel), 2020)
Paddies are a potential source of anthropogenic nitrous oxide (N(2)O) emission. In paddies, both the soil and the rice plants emit N(2)O into the atmosphere. The rice plant in the paddy is considered to act as a channel between the soil and the atmosphere for N(2)O emission. However, recent studies suggest that plants can also produce N(2)O, while the mechanism of N(2)O formation in plants is unknown. Consequently, the rice plant is only regarded as a channel for N(2)O produced by soil microorganisms. The emission of N(2)O by aseptically grown plants and the distinct dual isotopocule fingerprint of plant-emitted N(2)O, as reported by various studies, support the production of N(2)O in plants. Herein, we propose a potential pathway of N(2)O formation in the rice plant. In rice plants, N(2)O might be formed in the mitochondria via the nitrate–nitrite–nitric oxide (NO(3)–NO(2)–NO) pathway when the cells experience hypoxic or anoxic stress. The pathway is catalyzed by various enzymes, which have been described. So, N(2)O emitted from paddies might have two origins, namely soil microorganisms and rice plants. So, regarding rice plants only as a medium to transport the microorganism-produced N(2)O might be misleading in understanding the role of rice plants in the paddy. As rice cultivation is a major agricultural activity worldwide, not understanding the pathway of N(2)O formation in rice plants would create more uncertainties in the N(2)O budget.